Investigation of secondary formation of formic acid: urban environment vs. oil and gas producing region - Yuan, B.; Veres, P. R.; C Warneke; Roberts, J. M.; Gilman, J. B.; Koss, A.; Edwards, P. M.; Graus, M.; Kuster, W. C.; Li, S. -M.; Wild, R. J.; Brown, S. S.; et al. (ATMOSPHERIC CHEMISTRY AND PHYSICS, 2015)
Formic acid (HCOOH) is one of the most abundant carboxylic acids in the atmosphere. However, current photochemical models cannot fully explain observed concentrations and in particular secondary formation of formic acid across various environments. In this work, formic acid measurements made at an urban receptor site (Pasadena) in June-July 2010 during CalNex (California Research at the Nexus of Air Quality and Climate Change) and a site in an oil and gas producing region (Uintah Basin) in January-February 2013 during UBWOS 2013 (Uintah Basin Winter Ozone Studies) will be discussed. Although the VOC (volatile organic compounds) compositions differed dramatically at the two sites, measured formic acid concentrations were comparable: 2.3 +/- 1.3 in UBWOS 2013 and 2.0 +/- 1.0 ppb in CalNex. We determine that concentrations of formic acid at both sites were dominated by secondary formation (> 99 %). A constrained box model using the Master Chemical Mechanism (MCM v3.2) underestimates the measured formic acid concentrations drastically at both sites (by a factor of > 10). Compared to the original MCM model that includes only ozonolysis of unsaturated organic compounds and OH oxidation of acetylene, when we updated yields of ozonolysis of alkenes and included OH oxidation of isoprene, vinyl alcohol chemistry, reaction of formaldehyde with HO2, oxidation of aromatics, and reaction of CH3O2 with OH, the model predictions for formic acid were improved by a factor of 6.4 in UBWOS 2013 and 4.5 in CalNex, respectively. A comparison of measured and modeled HCOOH / acetone ratios is used to evaluate the model performance for formic acid. We conclude that the modified chemical mechanism can explain 19 and 45% of secondary formation of formic acid in UBWOS 2013 and CalNex, respectively. The contributions from aqueous reactions in aerosol and heterogeneous reactions on aerosol surface to formic acid are estimated to be 0-6 and 0-5% in UBWOS 2013 and CalNex, respectively. We observe that air-snow exchange processes and morning fog events may also contribute to ambient formic acid concentrations during UBWOS 2013 (similar to 20% in total). In total, 53-59 in UBWOS 2013 and 50-55% in CalNex of secondary formation of formic acid remains unexplained. More work on formic acid formation pathways is needed to reduce the uncertainties in the sources and budget of formic acid and to narrow the gaps between measurements and model results.